2022
DOI: 10.1001/jamanetworkopen.2022.0137
|View full text |Cite
|
Sign up to set email alerts
|

Use of Labor Neuraxial Analgesia for Vaginal Delivery and Severe Maternal Morbidity

Abstract: IMPORTANCEAddressing severe maternal morbidity (SMM) is a public health priority in the US. Use of labor neuraxial analgesia for vaginal delivery is suggested to reduce the risk of postpartum hemorrhage (PPH), the leading cause of preventable severe maternal morbidity. OBJECTIVE To assess the association between the use of labor neuraxial analgesia for vaginal delivery and SMM. DESIGN, SETTING, AND PARTICIPANTS In this population-based cross-sectional study, women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…For scheduled CS, Abe et al performed a nationwide population-based study to determine the association between the anesthesia method and SMM in a Japanese population and reported that GA was associated with increased SMM compared with NA (OR, 2.68; 95% CI, 1.97–3.64) [ 35 ]. Another population-based cross-sectional study including 575, 524 women demonstrated that NA for vaginal delivery was associated with a 14% decrease in the risk of SMM [ 36 ] and hence a lower risk of PPD.…”
Section: Discussionmentioning
confidence: 99%
“…For scheduled CS, Abe et al performed a nationwide population-based study to determine the association between the anesthesia method and SMM in a Japanese population and reported that GA was associated with increased SMM compared with NA (OR, 2.68; 95% CI, 1.97–3.64) [ 35 ]. Another population-based cross-sectional study including 575, 524 women demonstrated that NA for vaginal delivery was associated with a 14% decrease in the risk of SMM [ 36 ] and hence a lower risk of PPD.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of health care research, mediator variables interact with the association between the treatment and the outcome, explaining all or part of the association of the treatment with the outcome. Guglielminotti et al 3 found that that greater than one fifth of the association of neuraxial labor analgesia with SMM was mediated by the reduced risk of PPH. 3 The incidence of SMM has been increasing with time in the US.…”
Section: Openmentioning
confidence: 99%
“…Guglielminotti et al 3 found that that greater than one fifth of the association of neuraxial labor analgesia with SMM was mediated by the reduced risk of PPH. 3 The incidence of SMM has been increasing with time in the US. 1 However, a real-world problem is the disparity in maternal morbidity and mortality rates observed across the world 7 and also access to neuraxial labor analgesia for vaginal delivery, as Guglielminotti and colleagues alluded to, which may preclude our ability to generalize their findings to populations outside of the US.…”
Section: Openmentioning
confidence: 99%
See 2 more Smart Citations